Konsep Akidah dan Akhlak bagi Pejabat Publik: Perspektif Pendidikan Islam terhadap Integritas dan Tata Kelola Pemerintahan - Dika Kurnia Dikrillah; Ali Maulida (Yayasan Al-Afif, 2026)
This study examines the concepts of faith (akidah) and ethics (akhlak) as the foundation of leadership and governance with integrity from an Islamic perspective. The moral crisis plaguing modern bureaucracy marked by corruption, abuse of power, and a lack of integrity demands solutions that are not merely structural and legal in nature, but also spiritual and ethical. The study employs a qualitative analytical method using a literature review approach to sources from the Qur’an, Hadith, and contemporary academic literature in the fields of faith, ethics, and governance. The results of the study indicate that: (1) creed, particularly the concept of muraqabah (the awareness of being observed by Allah), functions as an effective internal control mechanism for public officials, (2) Islamic ethical values such as shidq (honesty), amanah (integrity), and ‘adl (justice) correspond directly with the principles of good governance, (3) the integration of faith and ethics into the legislative, executive, and judicial branches can serve as the foundation for clean, just, and accountable governance. This study concludes that strengthening the faith and ethics of public officials is a fundamental necessity in efforts toward Islamic, values, based bureaucratic reform.